Complete Evaluation of Adrenal Tumours in a Tertiary Care Institution in Thuringia, Germany - Askitis, D.; Kloos, C.; Battefeld, W.; Müller, N.; Wolf, G.; Dirsch, O.; Müller, U. A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Introduction and objective: Adrenal tumours, mainly incidentalomas, are an increasingly common clinical and diagnostic challenge. The aim of the present study was the retrospective evaluation of all patients with adrenal tumours treated in our university department from 1.1.1999–31.12.2013Patients and methods: 187 patients (108 females: 79 males, mean age 57.7 years) were found to have adrenal tumours in our institution during the study period. All patients underwent basic and, when indicated, advanced analytical testing for hormonal activity. Tumours were classified according to patients’ gender, age at diagnosis, tumour localization and size, as well as benignity and malignancy when postinterventional histopathological examination was conducted.Results: 134 (71.7%) patients had non-hormone secreting tumours, 17 (9.1%) pheochromocytoma, 13 (7.0%) Conn-syndrome, 13 (7.0%) adrenal Cushing’s disease, 1 congenital adrenal hyperplasia and 2 sexual hormone-secreting tumours. 7 (3.7%) tumours could not be definitively classified due to unclear or marginal test-results. Cushing’s disease was more prevalent in females (11 females: 2 males). 163 (87.2% of the total cohort) tumours were unilateral [95 (50.8%) left; 68 (36.4%) right] and 24 (12.8%) were bilateral. Tumour size was <3 cm in 109 (58.3%), 3–6 cm in 63 (33.7%) and >6 cm in 15 (8.0%) patients. 60 (32.1%) patients underwent adrenalectomy, thereof 88.9% of the patients with hormonally active tumours, while 8 (4.3%) were evaluated with ultrasound-guided biopsy. Malignancy was confirmed in 10 individuals (5.3%; 3 non-functioning tumours, 3 pheochromocytomas, 2 Cushing’s patients and 2 sexual-hormone secreting tumours), while 2 surgical specimens with histopathological diagnosis of pheochromocytoma showed signs of malignant changes. Benignity was histopathologically confirmed in 55 patients.Conclusions: The prevalence of detected adrenal tumours is rising due to widely available and applied abdominal imaging procedures. The vast majority of them are benign, of small size (<3 cm) and hormonally inactive. Adrenalectomy is the therapeutic method of choice in big and/or confirmed hormone-secreting tumours.